2015
DOI: 10.1175/jhm-d-14-0024.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TMPA-3B42 Versions 6 and 7 Precipitation Products with Gauge-Based Data over India for the Southwest Monsoon Period

Abstract: The upgraded version 7 (V7) of the Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) products is available to the user community. In this paper, two successive versions of the TMPA-3B42 research monitoring product, version 6 (V6) and V7, at the daily scale are evaluated over India during the southwest monsoon with gauge-based data for a 13-yr (1998-2010) period. Over typical monsoon rainfall zones, biases are improved by 5%-10% in V7 over the regions of higher rainfall li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…Compared to the 3B42V6 and 3B42RT, the 3B42V7 exhibited improvements in Bias, CC, RMSE, POD, FAR and CSI at all time periods, which was consistent with Overall, the performance of the precipitation estimates derived from gauge adjusted 3B42V7 product were better than that of its predecessor bias adjusted 3B42V6 and unadjusted 3B42RT products in the northern Pakistan. Compared to the 3B42V6 and 3B42RT, the 3B42V7 exhibited improvements in Bias, CC, RMSE, POD, FAR and CSI at all time periods, which was consistent with the findings in Bhutan [33], India [10], Morocco [13], and China [28]. Despite the fact that 3B42V7 showed superiorities over 3B42V6 and 3B42RT, it still exhibits poor agreements with the gauge-based reference data at daily and seasonal time scales as analyzed with lower values of CC.…”
Section: Accuracy Of Tmpa Products At Different Precipitation Intensisupporting
confidence: 80%
See 1 more Smart Citation
“…Compared to the 3B42V6 and 3B42RT, the 3B42V7 exhibited improvements in Bias, CC, RMSE, POD, FAR and CSI at all time periods, which was consistent with Overall, the performance of the precipitation estimates derived from gauge adjusted 3B42V7 product were better than that of its predecessor bias adjusted 3B42V6 and unadjusted 3B42RT products in the northern Pakistan. Compared to the 3B42V6 and 3B42RT, the 3B42V7 exhibited improvements in Bias, CC, RMSE, POD, FAR and CSI at all time periods, which was consistent with the findings in Bhutan [33], India [10], Morocco [13], and China [28]. Despite the fact that 3B42V7 showed superiorities over 3B42V6 and 3B42RT, it still exhibits poor agreements with the gauge-based reference data at daily and seasonal time scales as analyzed with lower values of CC.…”
Section: Accuracy Of Tmpa Products At Different Precipitation Intensisupporting
confidence: 80%
“…It is well reported that the accuracy of satellite-based precipitation products is dependent on precipitation variability, topography, and climate [6][7][8][9][10]. A large number of studies have evaluated the performance of 3V42V6 in many parts of world [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…are computed for continuous verification of multisatellite rainfall products. These skill metrics are recently used by Prakash et al (2014aPrakash et al ( , 2015 for the evaluation of different multisatellite rainfall products over the Indian …”
Section: Methodsmentioning
confidence: 99%
“…Daily, let alone hourly data, however, is not always available, and for ease of calculation Hajani et al [25] developed a set of regression equations using MAR data to estimate reliability and water savings anywhere in the peri-urban regions of Greater Sydney, Australia. Developments in satellite estimation of rainfall data where there is little or no ground data available [107][108][109][110] may also become a powerful tool in estimating potential yield, water savings and hence financial viability of a RWH system.…”
Section: Quantity Of Rainwater Harvestedmentioning
confidence: 99%